Pengenalan Strategi Digital Marketing untuk Usaha Mikro Kecil dan Menengah di Kelurahan Situ Gede, Kecamatan Bogor Barat, Kota Bogor - Muhammad Asyhar Agmalaro; Dea Amanda (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The development of digital technology, and internet has brought considerable changes to marketing activities. The marketing trends have been shifted from conventional to digital marketing. A proper digital marketing can reach target customers effectively and efficiently. The purpose of this activity is to help and enrich knowledge MSEM and provide an introduction to maximize the effectivet strategy to use digital technology in marketing MSME products in Situ Gede Village, West Bogor Sub-district, Bogor City. The introduction of digital marketing strategies for 15 selected MSMEs was carried out in the form of workshops and mentoring. This community service activity was started with the presentation of important points on digital marketing, followed by motivation with success stories of digital marketing by MSMEs, identification of the current technology utilization and digital marketing activities that have been carried out by participants, identification of obstacles and challenges encountered, and steps that need to be taken to overcome them. The active and enthusiastic participation of the participants in the discussion and mentoring group activities show that the knowledge and motivation of participants in adopsing digital marketinghave been succeed.